«Strategic triangle» Russia- India-China in international relations (theory and historical practice) - J. A. Mareeva (Vestnik MGIMO-Universiteta)
In article reconstructed the history of nomination and the fate of the idea of a «strategic triangle» of the three Eurasian giants - Russia, India and China (RIC); the foundations of the foreign policy and economic partnership of the three countries; examined the stages of the transformation of the idea of bringing them closer together in the geopolitical the project in the socio-political periodicals and scientific literature; the thesis about the prospects of institutional design RICK.